2020
DOI: 10.12973/eu-jer.9.1.433
|View full text |Cite
|
Sign up to set email alerts
|

An Explanation of Happiness with Secure Attachment, Basic Psychological Needs and Hope: The Case of Turkish University Students

Abstract: In this study we aimed to investigate the role of hope, secure attachment with the parents, and satisfaction levels of the basic psychological needs (autonomy, competence and relatedness) of university students in predicting their happiness levels. A total of 558 university students were recruited and 70% of them were female and 30% of them were male. Ages of the participants ranged from 18 to 29. The data were collected in classroom settings using personal information form, the Oxford Happiness Scale, the Att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 84 publications
(84 reference statements)
2
2
0
1
Order By: Relevance
“…It is considered important that the effect size of psychological autonomy taken from parents on resilience is lower than acceptance and involvement. This result is consistent with a few studies with different age groups in our country within the scope of the need for autonomy (Cihangir-Çankaya & Denizli 2020;Kandemirci, 2018) and autonomous self-construct (Özdemir, 2012). In studies conducted with children and young people living in Turkey indicated the proximity and the need to be associated, has been demonstrated to have a higher priority than autonomy needs.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It is considered important that the effect size of psychological autonomy taken from parents on resilience is lower than acceptance and involvement. This result is consistent with a few studies with different age groups in our country within the scope of the need for autonomy (Cihangir-Çankaya & Denizli 2020;Kandemirci, 2018) and autonomous self-construct (Özdemir, 2012). In studies conducted with children and young people living in Turkey indicated the proximity and the need to be associated, has been demonstrated to have a higher priority than autonomy needs.…”
Section: Resultssupporting
confidence: 92%
“…Anne babadan alınan psikolojik özerkliğin psikolojik sağlamlık üzerindeki etki büyüklüğünün, kabul ve ilgiye göre daha düşük olmasının önemli olduğu düşünülmektedir. Elde edilen bu sonuç ülkemizde farklı yaş gruplarıyla yapılan özerklik ihtiyacı (Cihangir-Çankaya & Denizli, 2020;Kandemirci, 2018) ve özerk benlik kurgusu (Özdemir, 2012) kapsamındaki birkaç araştırmayla tutarlılık göstermektedir. Belirtilen araştırmalarda da Türkiye'de yaşayan çocuk ve gençlerin yakınlık, ilişkili olma ihtiyaçlarının, özerklik ihtiyacından daha öncelikli olduğu ortaya konulmuştur.…”
Section: Discussionunclassified
“…Among social factors, greater BPNS is associated with improvements in both the ability to generate plans (pathways) and agency prospects among young Italians. This further substantiates prior findings showing that BPNS is relevant in increasing hope levels among young non-Italian people (Cankaya and Denizli 2020;Carmona-Halty et al 2019). However, our findings expand these prior results and are above what we had hypothesized, as all these needs are implied in strengthening hope dimensions.…”
Section: Resultssupporting
confidence: 91%
“…For instance, BPNS has shown positive moderate correlations among university students. Specifically, stronger hope perceptions were associated with higher perceived satisfaction of each of these basic needs, among young adults (Cankaya and Denizli 2020). Whole BPNS measures have been associated with stronger psychological capital, an aggregated measure of positive personal traits that encompasses hope (Carmona-Halty et al 2019).…”
Section: Hope and Social Relationships' Support Qualitymentioning
confidence: 99%
“…Apart from that, Taylor (Gallagher et al, 2021) states that the ability of adaptive coping style also influences hope. Another study was conducted by (Ouweneel et al, 2012;Yarcheski & Mahon, 2014;Muyan-Yılık & Demir, 2020;Cankaya & Denizli, 2020;Bryce et al 2020). Also, hope positively correlates with psychological adjustment, psychological well-being, and subjective well-being.…”
Section: Discussionmentioning
confidence: 99%